Multiple voices - Myers-Scotton, Carol (Blackwell Pub, 2006)
"Multiple Voices: An Introduction to Bilingualism provides a comprehensive overview of all major aspects of bilingualism. It is primarily concerned with bilingualism as a sociopolitical phenomenon in the world and, as such, emphasizes languages in contact, language maintenance and shift, language policy (including educational policies), and language as a social identity marker. Other topics discussed include the grammatical or cognitive aspects of bilingualism, such as codeswitching and convergence, how bilingualism appears to be organized in the brain, and how child bilingualism differs from bilingualism acquired at a later age." "Designed for upper-level undergraduate or beginning graduate students, this textbook includes many detailed examples from all over the world and is written accessibly by a prominent bilingualism researcher